2014
DOI: 10.1111/exd.12409
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin‐induced fibrosis in MC1 signalling‐deficient C57BL/6J‐Mc1re/e mice further supports a modulating role for melanocortins in collagen synthesis of the skin

Abstract: The melanocortin-1 receptor (MC 1 ) binds a-melanocytestimulating hormone (a-MSH) with high affinity and has a physiological role in cutaneous melanin pigmentation. Previously, we reported that human dermal fibroblasts also express functional MC 1 . a-MSH suppressed transforming growth factor-b 1 -and bleomycin (BLM)-induced collagen synthesis in vitro and in vivo.e/e mice, we tested as to whether MC 1 has a regulatory role on dermal collagen synthesis in the BLM model of scleroderma. Notably, mice with a C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Treatment with α-MSH by activating MC1-R in fibroblasts suppressed collagen deposition in experimental models of skin fibrosis, 17 whereas MC1R e/e mice showed increased formation of cutaneous type I collagen compared with WT mice in similar models. 18 These observations lend support to the concept that MC1-R might have a regulatory role also in aortic collagen synthesis and deposition. Extending this further to physiological consequences, we noted that aortic compliance, as evidenced by increased mechanical stiffness and pulse pressure, was compromised in MC1R…”
Section: Discussionsupporting
confidence: 63%
“…Treatment with α-MSH by activating MC1-R in fibroblasts suppressed collagen deposition in experimental models of skin fibrosis, 17 whereas MC1R e/e mice showed increased formation of cutaneous type I collagen compared with WT mice in similar models. 18 These observations lend support to the concept that MC1-R might have a regulatory role also in aortic collagen synthesis and deposition. Extending this further to physiological consequences, we noted that aortic compliance, as evidenced by increased mechanical stiffness and pulse pressure, was compromised in MC1R…”
Section: Discussionsupporting
confidence: 63%
“…They also confirmed the presence of POMC and the MC1R in affected skin from patients with SSc and dermal fibroblasts strongly expressed both POMC and MC1R [31]. In a recent study MC1-signalling-deficient mice were susceptible to bleomycin-induced fibrosis, whereas wild-type animals were not [32]. …”
Section: Discussionmentioning
confidence: 70%
“…Bleomycin‐induced murine scleroderma is a powerful tool for the investigation of fibrosis. In addition, recent studies have suggested other possible mechanisms of accelerated fibrosis by inhibiting adipogenesis through TGF‐ β 1 as well as the role of melanocortins in collagen synthesis using this model. Therefore, other new mechanisms are highly involved in the induction of fibrosis, and further studies are necessary.…”
Section: Discussionmentioning
confidence: 94%